Fifty Years of Studies on Greek Thought : Proceedings of the International Conference in Honour of Livio Rossetti - Ranocchia, Graziano; Rowe, Christopher J.; Tulli, Mauro (Classical Studies E-Books Online, Collection 2025., 2025)
The present volume collects the speeches given by renowned scholars during the International Conference Fifty Years of Studies on Greek Thought in honour of Livio Rossetti (Perugia and Bevagna, Italy, 18-20 September 2022). It is divided into four parts devoted respectively to the Presocratics, Eleatism, Plato, Socrates and the Socratic schools, and includes the laudatio pronounced by Ch. J. Rowe and the lectio magistralis delivered by L. Rossetti himself. The book aspires to represent, though only partially, the variety of scientific interests and the richness of interpersonal relationships woven in more than fifty years by Professor Rossetti.